Brahms and his poets a handbook - Loges, Natasha ca. 20./21. Jh (The Boydell Press, 2017)
Johannes Brahms's much-loved solo songs continue to be enjoyed in recordings and on recital stages all over the world. This book provides a wealth of information on the poets whose words he set, many of whom are still unfamiliar. A substantial introduction explores the multiple meanings song-poetry held for Brahms and challenges the widely held opinion that he responded only to the general mood of a poem. It is followed by alphabetically organised essays on the forty-six poets whose verses he set. Each summarises the settings, Brahms's links to the poet, interconnections between the poets, and offers further context situating the poet within a wider literary, cultural and political landscape. The poets are revealed to be part of a deeply collegial cultural community of which Brahms was an active part. Covering Brahms's 32 song opuses published during four decades of song-writing, this book offers a way of understanding what Brahms believed to be the right poetic basis for his immortal music. It is designed to be an essential reference tool for students and scholars of Johannes Brahms, as well as performers and lovers of his songs. - NATASHA LOGES is Head of Postgraduate Programmes at the Royal College of Music and has co-edited Brahms in the home and the concert hall: Between private and public performance and contributed to the Cambridge History of Musical Performance and is currently co-editing Johannes Brahms in Context. As a song accompanist, she has performed in various venues overseas and in the UK.